“Outsider”: The Influence of Migration Experience on the Life and Work of Hungarian-Canadian Songwriter B.B. Gábor - Kennedy, Victor; Kolar, Kristian; Bojnec Naterer, Neža (Hungarian Journal of English and American Studies, 2022)
This paper examines the life and work of Gábor Hegedűs, whose family escaped from the Russian invasion of Hungary in 1956, and settled in Toronto, Canada. Under the stage name B.B. Gábor, he wrote and released several successful songs and albums, many of which drew on his experience as a refugee, and were broadcast around the world, as well as in Canada. His most popular songs were satiric commentaries on culture and politics, comparing life in the USSR and in Canada. These were the themes that drew the most attention from audiences and critics, and earned them international airplay, most notably on Radio Free Europe. His difficulties coping with life as a refugee and as an immigrant to Canada resulted in personal tragedy, yet his ability to express these difficulties in his songs left a lasting legacy in both Canada and his native Hungary. (VK; KK; NBN)